Progress in Modern Marine Biomaterials Research - Yuliya Khrunyk; Slawomir Lach; Iaroslav Petrenko; Hermann Ehrlich (Marine Drugs, 2020)
The growing demand for new, sophisticated, multifunctional materials has brought natural structural composites into focus, since they underwent a substantial optimization during long evolutionary selection pressure and adaptation processes. Marine biological materials are the most important sources of both inspiration for biomimetics and of raw materials for practical applications in technology and biomedicine. The use of marine natural products as multifunctional biomaterials is currently undergoing a renaissance in the modern materials science. The diversity of marine biomaterials, their forms and fields of application are highlighted in this review. We will discuss the challenges, solutions, and future directions of modern marine biomaterialogy using a thorough analysis of scientific sources over the past ten years.